Feasibility of a stepped wedge cluster RCT and concurrent observational sub-study to evaluate the effects of modified ward night lighting on inpatient fall rates and sleep quality: a protocol for a pilot trial. Issue 1 (December 2016) - Chari, Satyan; Smith, Simon; Mudge, Alison; Black, Alex A; Figueiro, Mariana; Ahmed, Muhtashimuddin; Devitt, Mark; Haines, Terry
Abstract Background Falls among hospitalised patients impose a considerable burden on health systems globally and prevention is a priority. Some patient-level interventions have been effective in reducing falls, but others have not. An alternative and promising approach to reducing inpatient falls is through the modification of the hospital physical environment and the night lighting of hospital wards is a leading candidate for investigation. In this pilot trial, we will determine the feasibility of conducting a main trial to evaluate the effects of modified night lighting on inpatient ward level fall rates. We will test also the feasibility of collecting novel forms of patient level data through a concurrent observational sub-study. Methods/design A stepped wedge, cluster randomised controlled trial will be conducted in six inpatient wards over 14 months in a metropolitan teaching hospital in Brisbane (Australia). The intervention will consist of supplementary night lighting installed across all patient rooms within study wards. The planned placement of luminaires, configurations and spectral characteristics are based on prior published research and pre-trial testing and modification. We will collect data on rates of falls on study wards (falls per 1000 patient days), the proportion of patients who fall once or more, and average length of stay. We will recruit two patients per ward per month to a concurrent observational sub-study aimed at understanding potential impacts on a range of patient sleep and mobility behaviour. The effect on the environment will be monitored with sensors to detect variation in light levels and night-time room activity. We will also collect data on possible patient-level confounders including demographics, pre-admission sleep quality, reported vision, hearing impairment and functional status. Discussion This pragmatic pilot trial will assess the feasibility of conducting a main trial to investigate the effects of modified night lighting on inpatient fall rates using several new methods previously untested in the context of environmental modifications and patient safety. Pilot data collected through both parts of the trial will be utilised to inform sample size calculations, trial design and final data collection methods for a subsequent main trial. Trial registration Australian New Zealand Clinical Trials Register (ANZCTR): ACTRN12614000615684 (cluster RCT) and ACTRN12614000616673 (observational sub-study). Date Registered: 10 June 2014 (both studies). Protocol version: 1.2 (Dated: 01 June 2014) Anticipated completion: September 2015 Role of Trial Sponsor: The named sponsor for this investigator-initiated trial was the Director of the Royal Brisbane and Women's Hospital (RBWH) Safety and Quality Unit (Therese Lee, Phone: +61 7 3646 8111). The principal investigators, SC and MA, are employed by the RBWH Safety and Quality Unit. The trial sponsor has no involvement in any aspects of study design, conduct or decision to submit the report for publication. AM and MD are employed by other departments in the same organisation.